Odd Couples A History of Gay Marriage in Scandinavia - Rydström, Jens (Amsterdam University Press, 2011)
The concept of marriage as a union of a man and a woman was fundamentally challenged by the introduction of registered partnership in Denmark in 1989. "http://www.aup.nl/do.php?a=show_visitor_book&isbn=9789052603810">Odd Couples. A History of Gay Marriage in Scandinavia is the first comprehensive history of registered partnership and gay marriage in Scandinavia. It presents an outstanding study of the interaction between gay activism and traditional party politics. Based on interviews, parliamentary print and party documents, it gives a first-hand account of how the political stakeholders acted in a short and decisive period of Scandinavian history. The author traces the origins of laws which initially were extremely controversial - inside and outside the gay community - but have now gained broad popular and political support. The different experiences in all Scandinavian countries (Denmark -including Greenland and the Faroe Islands-, Norway, Sweden, Iceland, and Finland) are investigated in order to present a nuanced understanding of a fascinating political process that began in the 1960s and continues to change the ways we understand family, sexuality and nation.